Morpholine KECH-18D Restores Drug Sensitivity and Differentially Modulates Efflux Phenotypes in Cisplatin- and Paclitaxel-Resistant Cervical Cancer Cells - Clemente-Soto, Aldo F.; Cisneros-Hernández, Mireya; Duriez-Tizoc, Nidia L.; Bernal-Reynaga, Rodolfo; Maldonado-Domínguez, Mauricio; Romero-Ávila, Margarita; Parra-Unda, Jesús R.; Delgado-Vargas, Francisco; Martínez-Valenzuela, Marcela (Asian Pacific Journal of Cancer Biology, 2026)
Background: Chemoresistance represents a major obstacle in cancer therapy, often associated with enhanced drug efflux. This study aimed to generate and characterize cisplatin-resistance in C-33A cells (C-33A RCDDP), and included, for comparison, a previously established paclitaxel-resistant subline (C-33A RPTX) overexpressing transporters, such as ABCB1, ABCG4, and ABCC8. In addition, we assessed whether the morpholine KECH-18D could restore drug sensitivity by enhancing intracellular drug accumulation. Materials and Methods: C-33A RCDDP cells were developed by stepwise cisplatin (CDDP) exposure. Cytotoxicity assays of nine morpholines were carried out to identify structural determinants of anticancer activity in the C-33A cell line. Combinatorial assays with morpholine KECH-18D and CDDP or paclitaxel (PTX) were performed to determine whether KECH-18D chemosensitizes and retains the drug in C-33A RCDDP and C-33A RPTX cells. Results: C-33A RCDDP cells exhibited a 4.7-fold increase in CDDP resistance. C-33A RCDDP and C-33A RPTX cells both displayed cross-resistance patterns, but C-33A RTPX cells retained lower levels of the drug than C-33A RCDDP cells. Furthermore, KECH-18D maintained strong cytotoxicity against chemoresistant cell lines and enhanced the cytotoxicity of CDDP and PTX against them. Notably, KECH-18D increased drug accumulation in C-33A RCDDP cells in a time-dependent manner, but not in C-33A RPTX cells. Conclusion: In summary, C-33A RCDDP and C-33A RPTX cells developed different levels, and possibly mechanisms, of resistance. Because the morpholine KECH-18D resulted highly cytotoxic in both parental and chemoresistant cells, enhanced drug retention in C-33A RCDDP cells and increased the toxicity of CDDP or PTX in chemoresistant cells, KECH-18D is a promising scaffold for overcoming multidrug resistance by selectively modulating drug efflux-related and -unrelated phenotypes, though further studies are necessary to deep its mechanisms of action.